1985
DOI: 10.1037/0096-3445.114.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Mood, recall, and sensitivity effects in normal college students.

Abstract: In three experiments we explored the relation between normal variation in depressed mood and memory in college students. Subjects read and subsequently recalled stories whose protagonists experienced good, bad, and neutral events. Contrary to predictions arising independently from capacity theory and from schema theory, the recall of depressed and nondepressed subjects did not differ in either overall level or in affective content. The results are not easily handled by a conceptualization of depression, tied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
0
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 56 publications
(112 reference statements)
9
79
0
2
Order By: Relevance
“…In later work, Hasher, Rose, Zacks, Sanft, and Doren ( 1985) assessed depression in college students in a number of ways, including the BDI, and fo und no depressive deficits in the recall of stories. They concluded that studying stories of the type that they used is perhaps a task that is not difficult enough to show effort-related deficits.…”
Section: Na Turally Depressed Studentsmentioning
confidence: 99%
“…In later work, Hasher, Rose, Zacks, Sanft, and Doren ( 1985) assessed depression in college students in a number of ways, including the BDI, and fo und no depressive deficits in the recall of stories. They concluded that studying stories of the type that they used is perhaps a task that is not difficult enough to show effort-related deficits.…”
Section: Na Turally Depressed Studentsmentioning
confidence: 99%
“…Williams et al (1988 ) and Ellis and Ashbrook (1988) have suggested that well structured or organized materials make fewer processing demands. Recall of clearly structured prose passages like those used by Hasher, Rose, Zacks, Sanft, and Doren (1985) does not refle.ct depressive deficits, whereas recall of more obtuse text does (see Watts & Cooper, 1989). As early as 1976, Russell and Beekhuis showed that the ability to sort nouns into obvious categories during the learning task was not impaired by psychotic depression.…”
Section: Depressive Deficitsmentioning
confidence: 99%
“…Hertel and Rude (1991b) failed to replicate these findings with naturally depressed college students. (Also see Hasher et al, 1985;Ingram, 1989;Isen, 1984; for discussions of possible differences in memory effects associated with naturally occurring versus experimentally induced depression.) Recently, however, we have replicated the findings of Ellis et al (1984, Experiment 3) with clinically depressed outpatients.…”
Section: Depressive Deficitsmentioning
confidence: 99%
“…We have not, in fact, developed a post hoc explanation for the depressive advantage, believing that it requires replication before such speculations are worthwhile (see Hasher, Rose, Zacks, Sanft, & Doren, 1985, for a similar finding and interpretation). Instead, it is important to note that ef fort effects in free recall and response latencies were obtained for non depressed and depressed subjects alike-that a deficit in the recall of words from the more difficult contexts was clearly not experienced by naturally depressed students as it had been by students induced to feel depressed in the experiment by Ellis et al (1984).…”
Section: Recallmentioning
confidence: 99%